Urgensi Pengaturan Restitusi Digital dalam Menjamin Perlindungan Hukum Konsumen pada Transaksi E-Commerce di Indonesia - Zahwa Putri (Science and Education Journal (SICEDU), 2026)
This study aims to analyze the urgency of digital restaurant design in ensuring that consumers engaged in e-commerce transactions in Indonesia are protected by law. Rapid advancements in digital technology have increased the intensity of electronic system usage, but this has also heightened the risk of personal data breaches and misuse. The findings indicate that current protection mechanisms are largely reactive and focus more on administrative sanctions than on victim redress. Digital restitution is viewed as a relevant and adaptive concept to meet the demands of the digital era, both material and immaterial. Therefore, a more comprehensive approach to digital restitution needs to be developed to provide legal protection, enhance customer satisfaction, and create a more efficient and reliable data protection system in e-commerce.